Healthcare associated infections (HAI) perspectives - Jaffar A. Al-Tawfiq; Paul A. Tambyah (Elsevier, 2014)
Summary: Healthcare associated infections (HAI) are among the major complications of modern medical therapy. The most important HAIs are those related to invasive devices: central line-associated bloodstream infections (CLABSI), catheter-associated urinary tract infections (CAUTI), ventilator-associated pneumonia (VAP) as well as surgical site infections (SSI). HAIs are associated with significant mortality, morbidities and increasing healthcare cost. The cited case-fatality rate ranges from 2.3% to 14.4% depending on the type of infection. In this mini-review, we shed light on these aspects as well as drivers to decrease HAIs. Keywords: Healthcare associated infection, Hand hygiene